A multilevel perspective of transition to a circular economy with particular reference to a community renewable energy niche. (1st June 2020) - Finn, Jack; Barrie, Jack; João, Elsa; Zawdie, Girma
This article is an attempt to look into the processes involved in achieving full system transition to a circular economy (CE) through the development of niche activities. Based on a case study relating to a community renewable energy (CRE) niche, the article argues that for transition to take hold and make progress, the socio-technical regimes underpinning the system of a linear economy would need to be disrupted through the agency of niches that bring forth radical innovations across a spectrum of activities. This argument is explored through a case study from the energy sector in Scotland. A Delphi study is conducted to assess the success of the Scottish Government in progressing CRE as a niche aimed at disrupting the incumbent fossil-based energy regime. The study finds that despite the commitment of the Scottish Government to empower, nurture and shield CRE as a niche, there is no clear evidence as yet to show whether these actions have achieved their desired effect of enabling the CRE niche to play a disruptive role. The article also underscores the need for methodological refinement to enhance the robustness of the data used in the evaluation of policy efforts in niche development as a strategy for transition to CE.